Primary School Children’s Self-Reports of Attention Deficit Hyperactivity Disorder-Related Symptoms and Their Associations With Subjective and Objective Measures of Attention Deficit Hyperactivity Disorder - Slobodin, Ortal; Davidovitch, Michael (Frontiers in Human Neuroscience, 2022)
The diagnosis of Attention deficit hyperactivity disorder (ADHD) is primarily dependent on parents’ and teachers’ reports, while children’s own perspectives on their difficulties and strengths are often overlooked. To further increase our insight into children’s ability to reliably report about their ADHD-related symptoms, the current study examined the associations between children’s self-reports, parents’ and teachers’ reports, and standardized continuous performance test (CPT) data. We also examined whether the addition of children’s perceptions of ADHD-symptoms to parents’ and teachers’ reports would be reflected by objective and standardized data. The study included 190 children with ADHD, aged 7-10 years, who were referred to a paediatric neurologic clinic. A retrospective analysis was conducted using records of a clinical database. Obtained data included children’s self-reports of their attention level and ADHD-related symptoms, parent, and teacher forms of the Conners ADHD rating scales, Child Behaviour Checklist (CBCL), Teacher’s Report Form (TRF), and CPT scores. Results showed that children’s self-evaluations of their functioning were globally associated with their teachers’ and parents’ evaluations. However, children’s self- reports of their academic, social, and emotional difficulties were not uniquely associated with the same difficulties according to informants’ reports. Likewise, children’s self-reports of ADHD symptoms were not uniquely linked to a specific CPT impairment index, but to a general likelihood of having an impaired CPT. Our findings indicated that while ADHD children defined by one informant (parent or teacher) showed similar CPT profiles to ADHD children defined by two informants, the CPT performance successfully distinguished between these two groups and the group of children who also defined themselves as inattentive. Together, our findings suggest that primary school children with ADHD are able to reflect upon their difficulties and that their perspectives should inform clinical practice and research. The clinical and ethical imperative of taking children’s perspectives into account during ADHD diagnosis and treatment is highlighted.